Partial connections between ritual and performance in Bori : Oferenda à cabeça - Andrade Tinoco, Bianca; Felix Martins, Daniela (Ephemera: Revista do Programa de Pós-Graduação em Artes Cênicas da Universidade Federal de Ouro Preto, 2025)
This article analyzes intersections between the artistic and the religious in visual arts, focusing on Ayrson Heráclito’s performance Bori: Oferenda à cabeça (2008). It seeks to understand how the work mobilizes and reinterprets elements of Candomblé—especially the ritual of offering food to the orí (spiritual head)—in the field of contemporary art, creating friction between art and religion. To develop the analysis, documentation of the work prepared by the Pinacoteca de São Paulo, the catalog of the exhibition in which the performance was presented, and interviews given by the artist were examined, articulated with a theoretical-conceptual approach based on Marilyn Strathern’s reference of “partial connections.” In the performance, while alabês sing and play songs related to orixás, a performer composes crowns of raw and cooked foods on the heads of 12 artists lying on mats, who personify the children of different deities. The study emphasizes the subtleties of the preparation, activation, and demobilization of the performance, which highlight the symbolic complexity of transposing the ritual into the artistic realm. It argues that this process constructs an intricate game of analogies that, while reiterating the aesthetic dimension of the work, allows it to be understood as a space of mediation between rituality and artistic creation. Thus, Heráclito’s performance highlights the power of contemporary art to stretch disciplinary boundaries, while valuing knowledge and practices derived from Afro-Brazilian ancestry, contributing to broadening debates on memory, ritual, and representation in the arts.